Collaborative Retrospective Miscue Analysis: a pathway to self-efficacy in reading - Seeger, Victoria Nell (Kansas State University, 2009)
Collaborative Retrospective Miscue Analysis (CRMA) is a process where students participate in a small group discussion about their reading miscues, retellings, and thinking about reading. The purpose of this qualitative case study was to explore the self-efficacy beliefs students hold about their reading skills and abilities while engaged in CRMA. The six sixth- grade students audio taped their reading of text and followed by conducting an unassisted retelling. Next, the researcher transcribed the tapes providing students with a transcription during CRMA sessions. Students held discussions with their peers and the researcher about their reading miscues and retellings revealing their thinking about their miscues and examining why they occurred. Data from the videotaped CRMA sessions, Burke Reading Interviews, Self-Efficacy in Reading Scales, CRMA journals, and teacher e-mail interviews were extensively analyzed. Findings revealed changes in each of the participants’ self-efficacy in reading from the beginning to the end of the study. Analysis of the CRMA transcripts showed students held conversations from six areas: 1) initial discussions focusing on numbers of miscues or reading flawlessly; 2) discussion about reading strategies; 3) discussion about making sense of text; 4) discussion about miscues that affected meaning and those that did not; 5) discussion centered on the elements of retelling, and; 6) discussion finding strengths in peers’ skills. In addition, the transcripts revealed students discussed vocabulary from the text to build meaning during reading. Qualitative methods were employed to analyze multiple sources of data allowing students’ reading skills to be studied and examined in detail and the self-efficacy in reading that surfaced during the process. Thick, rich portraits of each student were developed looking through the following lenses: 1) prior literacy assessment; 2) Burke Reading Interviews; 3) miscue analysis; 4) retellings; 5) observational viewing; 6) the teacher’s lens; and, 7) developing self- efficacy in reading. Finally, a holistic group portrait was unveiled. Students deserve to be engaged in social learning, especially during reading when they can discuss their experiences with text with peers. CRMA provides a respectful avenue for students to talk about their miscues, retellings, and reading behaviors and nurture and extend self-efficacy in the process.
Keywords: Collaborative Retrospective Miscue Analysis; Retrospective Miscue Analysis; Reading; Self-Efficacy; Education, Reading (0535)